Perfil de biomarcadores no líquido Cefalorraquidiano de idosos sem comprometimento cognitivo objetivo e com Doença de Alzheimer - comprometimento cognitivo leve amnéstico e demência - Erika de Oliveira Hansen Pôrto (2021)
Background: Alzheimer's disease (AD) biomarkers are of great relevance in clinical research, especially after the AT(N) framework publication. They enable early diagnosis, disease staging and research with new promising drugs, monitoring its therapeutic response. However, the high cost and low availability of the most well-known methods limits their use in low and middle-income countries. In this context, semi-automated methodologies, such Luminex, stand out as a cost-effective technique. Recently, Fujirebio (Europe) suspended the commercialization of the INNOBIA AlzBio3 ®, that was the most used Luminex test. Therefore, others commercially available Luminex tests should be used, like Millipore xMap (HNABTMAG-68K) (Millipore, Germany). Objective: In our study, we assessed the diagnostic accuracy of Millipore xMap and propose a cutoff point for AD, based on INNOTEST. Methods: We performed a cross-sectional, case/control study, between March 2015 and November 2020. Thirty-five individuals over 60 years old were recruited and submitted to lumbar puncture. Seven older adults had a clinical diagnosis of AD’s dementia (ADD), 17 of amnestic mild cognitive impairment (aMCI) and 11 without objective cognitive impairment (control group - CG). Patients were classified according to clinical and biological criteria. Cerebrospinal fluid (CSF) biomarkers concentrations for Aβ42, p-Tau and t-Tau were measured by INNOTEST and Millipore xMap, and then the techniques were compared to assess the diagnostic accuracy of the new test and to define a cutoff. Results: There was agreement between clinical and biological diagnosis for 77,8% of patients, with 72,7% between CG (negative AD’s biomarker) and 85.7% between ADD (positive AD’s biomarker). Millipore xMap measurements showed a robust accuracy for all biomarkers, with AUC higher than 0,808 (t-Tau), and the best for Aβ42 (AUC=0,952). The most accurate cutoffs were found at 1012,98 pg/ml (Aβ42), 64,54 pg/ml (p-tau), 3251,81 pg/ml (t-tau), 3,370 (t-Tau/Aβ42) and 0,059 (p-Tau/Aβ42). Conclusion: Despite the small sample, Millipore xMap® proved to be an accurate test in relation to the INNOTEST® gold standard and has a significant lower cost. Given its good accuracy and cost-effectiveness, Milliplex xMap tests seem a reliable and promising tool, especially for low and middle-income countries.